IDENTIFICATION OF COASTAL BIOTA MANGROVE EDUCATION CENTER (MEC) USING LINE TRANSECT METHOD CASE STUDY IN PANGKALAN JAMBI VILLAGE, BUKIT BATU DISTRICT, BENGKALIS REGENCY - Tane, Bintang Rapshodio; Mulyadi, Aras; Haryanto, David M (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2022)
The Mangrove Education Center is located in Pangkalan Jambi Village, Bukit Batu Sei District. Pakning Bengkalis Regency which has the potential to be developed into a mangrove ecotourism area, because almost along the coast is overgrown with mangrove ecosystems and has abundant biota. This study aims to identify the potential of biota using the transect method as a mangrove ecotourism area. Data collection was carried out from January to February 2022 in Pangkalan Jambi. The research method used is purposive sampling. The research area was taken as many as 3 stations. Data analysis is based on the number of biota found in each station. Parameter data for mangrove tourism suitability consists of biota objects. The results of the measurement of the suitability of mangrove tourism parameters are the number of biota at station I with 35, station II at 30 and station III at 38. Found 4 species of biota with others such as: fish, shrimp, crabs, mollusks, reptiles, birds, and other biota. The results of this study indicate that this mangrove forest spans an area of ​​3 hectares along the coastline of Pangkalan Jambi Village. the most influential for the sustainability of the mangrove ecosystem.